Current limiter strategy of grid-connected pv system for LVRT Enhancement - Norazila, Jaalam; Nasrudin, Abd Rahim; Ab Halim, Abu Bakar (Springer Science and Business Media Deutschland GmbH, 2022)
A low-voltage ride-through (LVRT) is an ancillary service provided to a power grid to stabilize the grid voltage under weak grid conditions. Under these circumstances, a short-term disturbance is allowed to be ride-through to prevent unnecessary nuisance tripping during weak grid conditions. The main objective of this paper is to propose an active power curtailment strategy for a 1.038 MW grid-connected photovoltaic (PV) system to enhance the LVRT capability. A simple current limiter was applied to regulate the excessive DC-link voltage while the reactive power was controlled by a PI-tuning controller to maintain the voltage profile. Using MATLAB/Simulink environment, the dynamic behaviors of the proposed system were tested under 70% voltage sag and it was found that the proposed strategy is successful in curtailing the active power during low-voltage conditions and the excessive DC-link voltage can be controlled. Meanwhile, the whole system can maintain its operation without inverter disconnection and the voltage profile was improved even under weak grid conditions.